Meteostanice pro odlehlé lokality - Babovák, Adam (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Bakalářská práce se zabývá realizací meteostanice pro odlehlé lokality pomocí Arduino Nano mikrokontroleru a senzorů na měření teploty, tlaku, vlhkosti, srážek, rychlosti a směru větru. Dále se práce zaměřuje na spotřebu součástek a na zajištění napájení pomocí solárního panelu a baterie. Rešeršní část práce se zaměřuje na popis metod měření sledovaných veličin v meteorologii, na problematiku bezdrátové komunikace v odlehlejších lokalitách a na průzkum vhodných součástek a jejich charakteristik.

The bachelor thesis deals with the implementation of a weather station for remote locations using an Arduino Nano microcontroller and sensors for measuring temperature, pressure, humidity, precipitation, and wind speed and direction. Additionally, it focuses on the consumption of components and on providing power supply using solar panel and battery. The research part of the thesis focuses on the description of the measurement techniques in meteorology, on the issue of wireless communication in remote locations, and on the research of suitable components and their characterization.
Weather stations for outlying locations
Keywords: Meteorologie; meteostanice pro odlehlé lokality; Arduino mikrokontrolery; meteorologické měřicí techniky; Meteorology; weather stations for remote locations; Arduino microcontrollers; meteorological measuring techniques